Transferability of extended warranty in the presence of a P2P secondary market. (October 2021) - Zhang, Qi; Gao, Jie
Highlights: The extended warranty may be bundled with new products or be sold at a separate price. The transferability of extended warranty is considered in a P2P secondary market. We analyze the optimal decisions of prices and extended warranty. The manufacturer provides a transferable extended warranty bundled with new products when the warranty service cost is small. Abstract: In addition to the base warranty, many manufacturers offer the extended warranty, which may be bundled with new products or be voluntarily purchased by consumers at a separate price. Consumers may resell the used products in a peer-to-peer (P2P) secondary market in which the used products with extended warranty can attract more consumers. Thus, manufacturers need to decide whether the extended warranty can be transferred from the original owner to the buyer in the secondary market. In this paper, we develop an analytical model to investigate the manufacturer's optimal pricing decisions of the product and the extended warranty, as well as the transferability of extended warranty. Our results show that the manufacturer prefers to offer a transferable extended warranty when the warranty service cost is low, and prefers to provide a nontransferable extended warranty when the cost is high. The manufacturer can take an advantage of the optional extended warranty to segment the market. We also find that the manufacturer is more likely to provide a transferable extended warranty when the production cost is high or the used products fail at a high probability.